In vitro antiproliferative effects and underlying mechanismds of bismuth dithiocarbamate derivatives against breast cancer cell line - Chan, Pit Foong (2019)
Drastic increment of cancer incidence in recent years has driven metal complexes including bismuth complexes as a promising approach in anticancer drug development due to its well-known low toxicity, environmental friendliness and medical therapeutic benefits The complexes with R= (CH2CH2OH)(iPr), Et2, (CH2)4 and (CH2CH2OH)(CH3) in bismuth-dithiocarbamate, Bi[S2CN-R]3 labelled as C3, C4, C5 and C9, have been studied, respectively. This study aimed at determining the antiproliferative effect of the bismuth complexes and their underlying mechanism(s) in breast cancer cell (MCF-7) through various in vitro assays. The antiproliferative effect of the bismuth complexes was studied using Methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay. Apoptotic cell death activities of C3, C4, C5 and C9 were performed via DNA fragmentation, acridine orange/propidium iodide (AO/PI), Annexin V and caspase activity assays. Whilst, this study further employed Human Cancer Drug Targets RT² Profiler PCR array to study the expression of 84 actively sought targets for anticancer therapeutics and drug development to delineate the underlying mechanism(s). Results showed all tested compounds (C3, C4, C5 and C9) exhibited antiproliferative effects against MCF-7 cell line with IC50 of 10.33 ± 0.06 μM, 1.26 ± 0.02 μM, 1.07 ± 0.01 μM and 25.37 ± 0.12 μM, respectively. The morphology of apoptosis including formation of DNA fragments, phosphatidylserine translocation, chromatin condensation, and membrane blebbing was shown. The compounds were found to variably increase reactive oxygen species (ROS) generation thus increased mitochondrial membrane potential (MMP). Consequently, this led to the release of cytochrome c from mitochondria, demonstrated by the data obtained by flow cytometric analysis. All four tested compounds were revealed to induce both intrinsic and extrinsic apoptotic pathways, conferred by the data obtained from Human Cancer Drug Targets RT² Profiler PCR array, along with caspases activities assay. The compounds were also reported to significantly reduce several key gene expressions such as AKT1, BIRC5, CDK1 and NFκB1. The NF-κB signalling pathway was inhibited with the activation of Lys48-linked polyubiquitination thus led to NF-κB degradation. Conclusively, this study evidenced the anticancer property of C3, C4, C5 and C9 against breast cancer by initiating intrinsic and extrinsic apoptosis pathway and lays the foundation in the development of new bismuth based chemotherapeutic drugs.